(untitled) (Biological Sciences - PJSIR, 2003)
Five popular brands of chloroquine tablets available to the average Nigerian consumers were examined for the effects of Staphylococcus aureus and Bacillus cereus, on the dissolution , disintegration and hardness after six weeks of incubation. The maximum percent dissolution was 98.34 % with Bacillus subtiliswhile the minimum was 19.12% with Staphylococcus aureus. The disintegration results showed a maximum of 69 min. 19 sec with Staphylococcus aureus while the least was 56 sec with Bacillus subtilis. The maximum hardness obtained was 12.75 kg and the least was 1 .25kg also with Staphylococcus aureus. The dissolution, disintegration and hardness also varied with the control. The metabolic activities of the bacterial species were believed to have caused the variations in the physical properties of the chloroquine phosphate tablets. The results from this investigation strongly advises adequate storage of chloroquine phosphate tablets, especially when it is the drug of choice for the treatment of malaria in most endemic countries of sub-Saharan Africa.